An Italian affair - Fraser, Laura (Pantheon Books, 2001)
"Both travelogue and memoir," writing in the second person, the author tells of her impulsive affair with an aesthetics professor from Paris.--Cover.
Keywords: Fraser, Laura; Fraser, Laura -- Travel -- Italy; Divorced women -- United States -- Biography; Man-woman relationships -- Case studies; Italien; USA; Italy -- Description and travel; Biografie; Fallstudiensammlung